Mold contamination in schools with either high or low prevelance of asthma. Issue 1 (February 2015) - Vesper, Stephen; Prill, Rich; Wymer, Larry; Adkins, Lauren; Williams, Ronald; Fulk, Florence
Abstract Background Mold exposures have been linked to the development and exacerbation of asthma. The purpose of this study was to determine whether the Environmental Relative Moldiness Index (ERMI) metric, developed to quantify mold exposures in homes, might be applied to evaluating the mold contamination in schools. Methods Settled dust samples (n = 10) were collected on each level of a water‐damaged school in Springfield, Massachusetts and two samples per level in five Idaho schools. Each dust sample was analyzed for the 36 molds that make up the ERMI. The concentration of 2.5‐μm particulate matter (PM2.5) was measured in each school at two locations during the spring of 2013. Results The average ERMI value in the Springfield school, 15.51, was significantly greater (p < 0.001) than the average ERMI value, −2.87, in the Idaho schools. Ten of the twenty‐six Group 1 molds, which are associated with water‐damaged environments, were in significantly greater concentrations in the Springfield school. The populations of Group 2 molds, which are common indoors even without water damage, were essentially the same in Springfield and Idaho schools. The average PM2.5 concentration in the Springfield and Idaho schools was 11.6 and 3.4 μg/m3, respectively. Conclusions The ERMI scale might be useful in comparing the relative mold contamination in schools.